CO2 laser-induced weakening in chemically strengthened glass: Improvement in processability and its visualization by Raman mapping. Issue 3 (15th February 2018) - Terakado, Nobuaki; Uchida, Shohei; Sasaki, Ryusei; Takahashi, Yoshihiro; Fujiwara, Takumi
Abstract: Chemically strengthened glass has become essential in our daily lives and the demand is rapidly increasing in a variety of fields. However, the conventional cutting process is not applicable because of its tough layer with the compressive stress. To achieve higher-throughput production of the glass, we report spatially selective weakening of the compression layer by CO2 laser scanning and provide its visualization by Raman mapping. We demonstrate cutting the scanned glass without shattering using a typical scribing wheel. Finally, we discuss the improvement in processability from the viewpoint of microscopic structures by means of thermal analysis and Raman spectroscopy.